Tipping point analysis of cracking in reinforced concrete. (11th December 2015) - Perry, M; Livina, V; Niewczas, P
Abstract: In this work, we demonstrate that tipping point analysis of strain data can provide reactive and predictive indicators of cracking and structural transitions in a reinforced concrete system. The method is able to detect trend-driven transitions in a short time series of approximately 2000 datapoints, providing a clear indication of when a concrete beam under gradual bending progresses from a linear to a nonlinear strain response. The method is also able to provide an early warning signal of the appearance of bifurcations, such as cracks, with a forewarning of 200–500 datapoints. The method, which was originally developed for applications in geophysics, shows promising results in the area of structural health monitoring, in particular, for real-time observations of civil constructions.